PENGARUH KOMITMEN ORGANISASI, MOTIVASI KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI HONOR LEPAS PADA PUSKESMAS DI KABUPATEN MOROWALI - Salma, Salma (Katalogis, 2016)
This research aims to analyze the influence of organizational commitment, work motivation and work experience on the performance of temporary employees at the health centers in Morowali Regency. Through purposive sampling, this research selects 84 temporary employees in three health centers that are : Bahomotefe, Bahonsuai and Laantula Jaya, as respondents. The result of multiple linear regressions test show that : 1) organizational commitment, work motivation and work experience simultaneously have positive and significant influence on the performance of temporary employees; 2) organizational commitment positively influences the performance of temporary employees, but insignificant; 3) work motivation positively influences the performance of temporary employees, but insignificant; 4) work experience positively and significanly influences the performance of temporary employees; 5) work experience has dominant influence on temporary employees’ performance.